HUBUNGAN PELAKSANAAN HIGIENE SANITASI DAN KANDUNGAN BAKTERIOLOGI DEPOT AIR MINUM ISI ULANG DI KABUPATEN SIJUNJUNG TAHUN 2021 - Yuswir, Atasia Degita; Suharti, Netti; Bahar, Elizabeth; Julizar, Julizar (SINERGI : Jurnal Riset Ilmiah, 2025)
The Sijunjung District Health Office recorded 152 refill drinking water depots but in 2021 there were only 38 active refill drinking water depots. Of the 38 active refill drinking water depots, 18 refill drinking water depots were not eligible. Of the refill drinking water depots that did not eligible, there were 17 refill drinking water depots contaminated with bacteriology and 1 drinking water depots was not to not eligible the physical requirements. Drinking water contaminated with bacteriology can cause gastrointestinal diseases, one of which is diarrhea. The number of diarrhea sufferers in Sijunjung Regency in the last 3 years has peaked in 2021, 10,974 people. However, until now there has been no data analysis on the results of the implementation of refill drinking water depot’s hygiene and sanitation in accordance with the conditions of each refill drinking water depots so that the counseling carried out has not focused on the priority problems being faced and can have an impact on the quality of drinking water produced. This study is a secondary data survey research from the results of drinking water inspection by the Regional Health Laboratory and the results of the implementation of sanitation hygiene by the Puskesmas at 38 refill drinking water depots in Sijunjung Regency which were analyzed by chi-square test to assess the relationship between variables. The results of this study found that the majority of refill drinking water depots were contaminated with Coliform and E.coli (31.6%). According to the implementation of refill drinking water depot’s sanitation hygiene, only the place aspect (2.6%), the equipment aspect (94.7%), the handler aspect (21.1%), and the raw water aspect (21.1%). In addition, there was no relationship between the equipment aspect (p=0.878) and the handler aspect (p=0.643) and it was not possible to determine the relationship between the place aspect and the raw water aspect to the bacteriological content of refill drinking water depots